Informal Learning of English at University: a cross-sectional and longitudinal perspective - De Riso, Camilla (Materiali Linguistici, 2025)
With English increasingly moving out of the classroom and into informal settings, studies on informal second language learning (ISLL) have supplied evidence on how prolonged exposure to informal L2 input can enhance advanced receptive and productive skills in L2 learners. This book explores how Italian university students spontaneously access English, drawing on a survey to analyze their exposure to various types of informal input and motivations for engaging with the language. A longitudinal study further observed four participants' L2 spoken production over time, assessing complexity, accuracy and fluency (CAF) trajectories in relation to frequency, intensity and type of exposure. Findings reveal shifting access patterns among younger generations, highlighting the role of informal L2 input in shaping new acquisitional profiles. Frequent exposure to English is no longer exclusive to language specialists or advanced L2 speakers. Moreover, the longitudinal case studies show strong variability across participants and within individual L2 development, influenced by individual differences and specific elements such as immersion and register